Exploring Women's Beliefs and Perceptions About Healthy Eating Blogs: A Qualitative Study - Bissonnette-Maheux, Véronique; Provencher, Veronique; Lapointe, Annie; Dugrenier, Marilyn; Dumas, Audrée-Anne; Pluye, Pierre; Straus, Sharon; Gagnon, Marie-Pierre; Desroches, Sophie (JMIR Publications, 2015)
BackgroundChronic diseases are the leading cause of death (63%) worldwide. A key behavioral risk factor is unhealthy eating. New strategies must be identified and evaluated to improve dietary habits. Social media, such as blogs, represent a unique opportunity for improving knowledge translation in health care through interactive communication between health consumers and health professionals. Despite the proliferation of food and lifestyle blogs, no research has been devoted to understanding potential blog readers' perceptions of healthy eating blogs written by dietitians. ObjectiveTo identify women's salient beliefs and perceptions regarding the use of healthy eating blogs written by dietitians promoting the improvement of their dietary habits. MethodsWe conducted a qualitative study with female Internet users living in the Quebec City, QC, area with suboptimal dietary habits. First, the women explored 4 existing healthy eating blogs written in French by qualified dietitians. At a focus group 2-4 weeks later, they were asked to discuss their experience and perceptions. Focus group participants were grouped by age (18-34, 35-54, and 55-75 years) and by their use of social media (users/nonusers). Using a questionnaire based on the Theory of Planned Behavior, participants were asked to identify salient beliefs underlying their attitudes (advantages/disadvantages), subjective norms (what people important to them would think), and perceptions of control (facilitators/barriers) regarding the use of a healthy eating blog written by a dietitian to improve dietary habits. Discussion groups were audiotaped, transcribed verbatim, coded, and a deductive content analysis was performed independently by 2 individuals using the NVivo software (version 10). ResultsAll participants (N=33) were Caucasian women aged between 22 to 73 year. Main advantages perceived of using healthy eating blogs written by a dietitian were that they provided useful recipe ideas, improved lifestyle, were a credible source of information, and allowed interaction with a dietitian. Disadvantages included increased time spent on the Internet and guilt if recommendations were not followed. Important people who would approve were family, colleagues, and friends. Important people who could disapprove were family and doctors. Main facilitators were visually attractive blogs, receiving an email notification about new posts, and finding new information on the blog. Main barriers were too much text, advertising on the blog, and lack of time. ConclusionsThe women in this study valued the credibility of healthy eating blogs written by dietitians and the contact with dietitians they provided. Identifying salient beliefs underlying women's perceptions of using such blogs provides an empirically supported basis for the design of knowledge translation interventions to help prevent chronic diseases.